Polyarylether‐Based 2D Covalent‐Organic Frameworks with In‐Plane D–A Structures and Tunable Energy Levels for Energy Storage. Issue 6 (26th December 2021) - Li, Nana; Jiang, Kaiyue; Rodríguez‐Hernández, Fermín; Mao, Haiyan; Han, Sheng; Fu, Xiaobin; Zhang, Jichao; Yang, Chongqing; Ke, Changchun; Zhuang, Xiaodong
Abstract: The robust fully conjugated covalent organic frameworks (COFs) are emerging as a novel type of semi‐conductive COFs for optoelectronic and energy devices due to their controllable architectures and easily tunable the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) levels. However, the carrier mobility of such materials is still beyond requirements due to limited π ‐conjugation. In this study, a series of new polyarylether‐based COFs are rationally synthesized via a direct reaction between hexadecafluorophthalocyanine (electron acceptor) and octahydroxyphthalocyanine (electron donor). These COFs have typical crystalline layered structures, narrow band gaps as low as ≈0.65 eV and ultra‐low resistance (1.31 × 10 −6 S cm −1 ). Such COFs can be composed of two different metal‐sites and contribute improved carrier mobility via layer‐altered staking mode according to density functional theory calculation. Due to the narrow pore size of 1.4 nm and promising conductivity, such COFs and electrochemically exfoliated graphene based free‐standing films are fabricated for in‐plane micro‐supercapacitors, which demonstrate excellent volumetric capacitances (28.1 F cm −3 ) and excellent stability of 10 000 charge–discharge cycling in acidic electrolyte. This study provides a new approach toward dioxin‐linked COFs with donor‐acceptor structure and easily tunable energy levels for versatile energy storage and optoelectronic devices. Abstract : A series of polyarylether‐based 2D covalent‐organic frameworks with in‐plane donor–acceptor structure and tunable energy levels are rationally synthesized. These materials show possible AA stacking with conduction band and also show excellent volumetric capacitance of up to 28.1 F cm −3 .